Taper corrosion in total hip arthroplasty: how to assess and which design features are crucial? - Müller, Ulrike; Bormann, Therese; Schröder, Stefan; Renkawitz, Tobias; Kretzer, Jan Philippe (Journal of the mechanical behavior of biomedical materials, 2022)
Background - In total hip replacement, wear and corrosion arising from modular taper connections have increasingly become a serious clinical concern. Previous studies led to confounding results regarding the role of specific taper design features, likely due to the application of different analytical approaches. Accordingly, this study has two major objectives: first, to evaluate different analytical approaches to evaluate the fretting-corrosion behavior; and secondly to determine the effect of four specific design variables: the taper engagement situation, the stem taper length and surface topography in terms of roughness and contact ratio. - Methods - An in vitro fretting-corrosion test setup was used including an aggressive solution. Cyclic loading was applied, varying from 300 N to 2500 N at a frequency of 3 Hz. Taper dummies covering different implant designs were tested in seven different test groups. Different quantitative and qualitative analytical test methods such as electrochemical characterization, ion analysis, gravimetry and corrosion scoring were applied in order to quantify the material degradation. - Results - A stepwise linear regression analysis showed that the taper engagement situation is the predominant factor that predicts the metal ion release from the taper connection, followed by the contact ratio of the taper surface and subsequently the taper length. A distal taper engagement situation, as well as a high contact ratio and a short taper length are the relevant parameters that decrease the metal ion release. Hereby, metal ion analysis turned out to be the most precise and reliable method for determining corrosive driven material loss, followed by gravimetry. - Conclusion - It was found that the taper engagement length is the major design parameter that influences the total ion release. It further turned out, that the selection of an appropriate analytical approach is essential for the evaluation of the corrosion behavior of taper connections in an experimental setting.
Gesehen am 26.07.2022